STRESSFUL LIFE EVENTS OF PATIENT WITH ISCHEMIC HEART DISEASE AT AL-NASIRIYA HEART CENTER - Khasal, Qasim Ali; Al Sadoon, Ied; Shinjar, Fatima J (International Journal of Psychosocial Rehabilitation, 2020)
At present, the cardiovascular diseases (CVD) are among the major concerns of World Health Organization (WHO), assurance health systems and researchers in the specific field, because they are the number one cause of deaths globally, and according to several perspective studies, they will become the pathology that generates the greatest economic burden worldwide, through morbidity, disability, poor quality of life, and cause of death. Nowadays, the psychic field and the vulnerability of individual mental level to stress are an important link in the development of mental illness, CVD (included in the group of psychosomatic disorders), and also of interrelationship between them. Objectives: 1.To assess the stressful life events of adult patients with ischemic heart disease (IHD) .2. To find out the relationship between stressful life events and socio-demographical characteristics (age, gender, marital status, and socioeconomic status) of adult patients with ischemic heart disease. Methodology: A descriptive study was carried out to assessment of stressful Life events of patient with coronary artery disease at al-Nasiriya Heart Center. A purposive (non-probability) sample of (100) patients. The study population consisted of a sample of adults from both genders whose ages were 30 years and more, and were newly diagnosed as having CAD by coronary angiography in the cardiac catheterization unit An Nasiriyah heart center.Reliability of the questionnaire form was determined through a pilot study while the content validity of the questionnaire was determined through a panel of experts. And then the Data were collected through the use of the observational tool (questionnaire ), which was analyzed through the use of three statistical approaches. They are descriptive statistical analysis (frequencies, percentage, S.D, range of scores, mean of scores and relative sufficiency; inferential statistical analysis (correlation coefficient and chi- square test); and analysis of variance (ANOVA).Results: high percentage (55%) of the study sample have myocardial infarction. The advancing age of the patients ( 50 years & more ) is one of the most common non-modifiable risk factors. Most of the patients 78(78%) were male .The majority of the patients 84 (84 %) were married. Lower educated patients have a higher risk to develop coronary arteries disease than the Higher educated patients . High percentage (30%) of patients were Unemployed. The result of the present study indicates that most of the patients (40%) were suffering from Insufficient income . The result of the present study indicates that the majority of the patients (78%) were living in rural . Most of the patients feel stress because of the economic situation and the percentage, were (35%) of patients. There were no statistical significant differences were found between stress management with all socio- demographic characteristic except age.